2023
DOI: 10.4110/in.2023.23.e35
|View full text |Cite
|
Sign up to set email alerts
|

CD5 Expression Dynamically Changes During the Differentiation of Human CD8+ T Cells Predicting Clinical Response to Immunotherapy

Young Ju Kim,
Kyung Na Rho,
Saei Jeong
et al.

Abstract: Defining the molecular dynamics associated with T cell differentiation enhances our understanding of T cell biology and opens up new possibilities for clinical implications. In this study, we investigated the dynamics of CD5 expression in CD8 + T cell differentiation and explored its potential clinical uses. Using PBMCs from 29 healthy donors, we observed a stepwise decrease in CD5 expression as CD8 + T cells progressed through the differentiation stages. Interesti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Understanding the molecular dynamics of T cell differentiation contributes to advancing our knowledge of T cell biology and opens up new possibilities for clinical applications. In a retrospective analysis of non-small cell lung cancer (NSCLC) patients receiving anti-PD-1/PD-L1 therapy, patients with higher expression of CD5 on their effector memory T cells (Tem) showed improvement in response to anti-PD-1/PD-L1 therapy compared to those with lower CD5 expression [33] . Similarly, studies have demonstrated that Treg cells inhibit the activity of NK and CD8 + T cells through the GZMB-perforin pathway, and GZMB-deficient mice are more effective than wild-type (WT) mice in clearing both allogeneic and syngeneic tumor cell lines [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the molecular dynamics of T cell differentiation contributes to advancing our knowledge of T cell biology and opens up new possibilities for clinical applications. In a retrospective analysis of non-small cell lung cancer (NSCLC) patients receiving anti-PD-1/PD-L1 therapy, patients with higher expression of CD5 on their effector memory T cells (Tem) showed improvement in response to anti-PD-1/PD-L1 therapy compared to those with lower CD5 expression [33] . Similarly, studies have demonstrated that Treg cells inhibit the activity of NK and CD8 + T cells through the GZMB-perforin pathway, and GZMB-deficient mice are more effective than wild-type (WT) mice in clearing both allogeneic and syngeneic tumor cell lines [34] .…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the molecular dynamics of T cell differentiation advances our knowledge of T cell biology and opens new possibilities for clinical applications. In a retrospective analysis of non-small cell lung cancer (NSCLC) patients undergoing anti-PD-1/PD-L1 therapy, those with higher CD5 expression on their effector memory T cells (Tem) showed improved responses compared to those with lower expression (Kim et al 2023 ). Studies also show that Treg cells inhibit the activity of NK and CD8 + T cells through the GZMB-perforin pathway, and GZMB-deficient mice are more effective in clearing both allogeneic and syngeneic tumor cell lines (Cao et al 2007 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, CD5 was shown to function as a negative regulator of the IL-15 response in memory CD8 + T cells ( 66 ). The expression of CD5 on human CD8 + T cells progressively decreases during cellular differentiation and senescence ( 68 69 ). Consequently, highly differentiated and senescent memory CD8 + T cells with low expression of CD5 exhibit a heightened responsiveness to IL-15, revealing an inverse correlation between the level of CD5 expression and IL-15 responsiveness.…”
Section: Il-15 and T-cell Responsesmentioning
confidence: 99%